Regulating medical bodies? The consequences of the ‘modernisation’ of the NHS and the disembodiment of clinical knowledge - Nettleton, Sarah; Burrows, Roger; Watt, Ian (Sociology of health & illness, 2008)
The aim of this paper is to explore the consequences of modernisation and regulatory processes for the everyday lives of doctors working the UK National Health Service. We do this by reporting on interview data generated as part of a qualitative investigation into the working lives of 47 doctors. The analysis of the empirical findings is informed by two literatures: that which has sought to theorise the contemporary thrust of regulation and audit and that which has developed a sociology of embodiment. Doctors’ views are presented in relation to four areas of work which have – in the loosest sense of the word – been subject to regulation. Drawing on work from the sociology of embodiment we argue that changes in the institutional and cultural context of medical work could be altering both the ‘field’ and the ‘habitus’– to use Bourdieu's terms – of medicine, with a consequence that medical knowledge is becoming less embodied.